Surface modification with ionic liquid for efficient CsPbI2Br perovskite solar cells - Xingyu Pu; Jian Han; Shuangjie Wang; Hui Zhou; Qi Cao; Jiabao Yang; Ziwei He; Xuanhua Li (Journal of Materiomics, 2021)
The presence of numerous trap states on the perovskite surface severely affects the performance of inorganic CsPbI2Br perovskite solar cells. Surface modification has been proven to be an effective strategy to passivate the surface trap states of CsPbI2Br perovskite. However, most modifiers behave high volatility and insulation, not enough to further develop the CsPbI2Br solar cells. Herein, an ionic liquid of 1-viny-3-propionate ethyl imidazolium chloride ([PEVIM]Cl) is applied to modify the CsPbI2Br film surface, yielding a compact film with enhanced crystallinity. The surface trap states of CsPbI2Br film are effectively passivated via the interaction between carbonyl group of [PEVIM]Cl and uncoordinated metal cations of CsPbI2Br perovskite, leading to charge recombination suppression and charge transport enhancement. Consequently, the power conversion efficiency (PCE) of [PEVIM]Cl modified CsPbI2Br device is obviously enhanced from 12.49% to 14.19% with an improved open-circuit voltage of 1.160 V. Moreover, the non-encapsulated device presents excellent thermal stability, still maintaining 91% PCE when heated at 85 °C in nitrogen atmosphere for 360 h. Meanwhile, the non-encapsulated device degrades only 11% PCE after stored at 50% relative humidity for 960 h. This simple and efficient approach provides a promising direction to fabricate high-efficiency and stable inorganic perovskite devices.